Environmental service-learning approach in higher education – a descriptive case study on student-led life cycle assessments of university cafeteria meals - Johannisson, Jonas; Hiete, Michael (International journal of sustainability in higher education, 2021)
Purpose This study aims to share experiences of an easy to adapt service-learning approach in a graduate course on life cycle assessment (LCA). Specifically, it reports on how students helped the university’s cafeteria to assess meals by conducting an LCA for 25 meals and identifying environmental hotspots. Design/methodology/approach A descriptive case study of a graduate course at Ulm University is presented. The course included lectures and problem-based exercises, both theoretical and software assisted. A course evaluation was conducted during the course and one year after completion to poll improvement potentials, as well as its impacts on students’ everyday life. Findings It was found that although it was the first LCA for all students, the resulting LCA information of 25 different meals were homogeneous, comparable to the scientific literature and beneficial to the cafeteria’s sustainable development strategy. The concept of service-learning had a higher impact on students’ motivation than a good grade and active-learning is explicitly requested by students. The course design sensitized students to the real-life problems of LCA and made their consumption patterns more elaborate and ecological. Furthermore, this digitization of higher education could be carried out with only minor changes in the present COVID-19 pandemic situation. Originality/value As the subject of service-learning in natural sciences is still expandable, this study presents an easy to adapt case study on how to integrate such an approach into university curricula dominated by traditional learning. To the best of the authors’ knowledge, this case study presents the first published LCA university course explicitly describing and evaluating a service-learning approach. The topic touches the everyday lives of students, allows comparisons between different student groups, is easily scalable to different group sizes and credits, and supports learning both how to study in small groups and cooperation between groups to ensure comparability of LCA results.